2018
DOI: 10.1111/aji.12993
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome in normal and pathological pregnancies: A literature overview

Abstract: This review summarizes recent findings on the changes that occur during pregnancy in the composition of the vaginal and gut microbiome and their association with metabolic, hormonal, and immunological factors. Despite many studies on the topic, the vaginal and gut microbial profiles and their influence on the course of pregnancy are still unclear. We present data suggesting that, contrary to traditional understanding, the placenta is not sterile but has a microbial community. We review and discuss new findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 94 publications
1
40
0
6
Order By: Relevance
“…While relatively few studies have examined this question in the context of pregnancy, evidence from studies in the nonpregnant state suggest that commensal organisms are involved in the programming of peripheral and local immune tolerance via a plethora of mechanisms, including endotoxin tolerance [17,168] and induction of Tregs by bacterial metabolites [93,166]. Several longitudinal studies have recently investigated the changes in maternal vaginal and gut microbiota during pregnancy, which are potential contributors to the immune clock of pregnancy [42,88,102,147,175]. These studies have yielded incongruous results, which likely reflect differences in demographic and/or genetic factors between studies.…”
Section: Microbiome Regulation Of Immune Responses In Pregnancymentioning
confidence: 99%
“…While relatively few studies have examined this question in the context of pregnancy, evidence from studies in the nonpregnant state suggest that commensal organisms are involved in the programming of peripheral and local immune tolerance via a plethora of mechanisms, including endotoxin tolerance [17,168] and induction of Tregs by bacterial metabolites [93,166]. Several longitudinal studies have recently investigated the changes in maternal vaginal and gut microbiota during pregnancy, which are potential contributors to the immune clock of pregnancy [42,88,102,147,175]. These studies have yielded incongruous results, which likely reflect differences in demographic and/or genetic factors between studies.…”
Section: Microbiome Regulation Of Immune Responses In Pregnancymentioning
confidence: 99%
“…Nasioudis et al evaluated relative abundance of bacteria in the vaginal microbiome in firsttrimester pregnant women, and the results showed that L. crispatus was the numerically most abundant bacterium in 76.4% of women with a first conception, 50.0% with only a prior spontaneous or scheduled abortion, and 22.2% with a prior birth; L. iners was the most abundant bacterium in 3.8% of women with a first conception as compared to 19.2 and 20.8% in those with a prior abortion or birth, respectively; Gardnerella as the most abundant bacterial genus increased from 3.8% in women with a first conception to 15.4 and 14.3% in those with a prior abortion or birth, respectively (24). High estrogen during pregnancy is also another factor because a high estrogen level can induce lactobacilli to more efficiently utilize the vaginal epithelium to decompose glycogen and lactic acid, and a low vaginal pH is optimal for lactobacilli and eliminates the invasion of other harmful bacteria (24,25). Therefore, Gjerdingen et al claim that vaginal pH can be a predictive index of vaginal infection in pregnant women (26).…”
Section: Introductionmentioning
confidence: 99%
“…The vaginal mucosa is a barrier that provides protection against invading pathogens, as a result of the interaction between its epithelial cells, the immune system, and symbiotic microorganisms (79). The microbiota residing in the vaginal space are an active critical component in such defense system against infections.…”
Section: Vaginal Protection By Lactobacillimentioning
confidence: 99%
“…Alteration of the ecology of the female reproductive tract has been linked to maternal and fetal health, and to adverse pregnancy outcomes (27,79,144,145). The most widely studied pregnancy complication in relation to the vaginal microbiota is preterm birth (PTB) (146)(147)(148).…”
Section: Late Pregnancy (Premature Delivery Premature Rupture Of Memmentioning
confidence: 99%